2011
DOI: 10.1186/1476-511x-10-194
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue endocannabinoid system gene expression: depot differences and effects of diet and exercise

Abstract: BackgroundAlterations of endocannabinoid system in adipose tissue play an important role in lipid regulation and metabolic dysfunction associated with obesity. The purpose of this study was to determine whether gene expression levels of cannabinoid type 1 receptor (CB1) and fatty acid amide hydrolase (FAAH) are different in subcutaneous abdominal and gluteal adipose tissue, and whether hypocaloric diet and aerobic exercise influence subcutaneous adipose tissue CB1 and FAAH gene expression in obese women.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 25 publications
0
39
0
1
Order By: Relevance
“…Almost no research has been conducted to directly examine the effects of chronic exercise training on the eCB system in humans, and the few studies that have examined eCB levels as a secondary aim of their projects have found conflicting results (4649). Relevant to its presence in reward-processing brain regions, though, one study found that plasma AEA concentrations were significantly lower at baseline, after acute exercise, and after 2 weeks of inactivity in runners categorized as “exercise dependent” (based on the Exercise Dependence Scale, which incorporates the DSM-IV criteria for substance abuse and dependence) compared to runners who did not meet the criteria for exercise dependence (50).…”
Section: The Endocannabinoid Systemmentioning
confidence: 99%
“…Almost no research has been conducted to directly examine the effects of chronic exercise training on the eCB system in humans, and the few studies that have examined eCB levels as a secondary aim of their projects have found conflicting results (4649). Relevant to its presence in reward-processing brain regions, though, one study found that plasma AEA concentrations were significantly lower at baseline, after acute exercise, and after 2 weeks of inactivity in runners categorized as “exercise dependent” (based on the Exercise Dependence Scale, which incorporates the DSM-IV criteria for substance abuse and dependence) compared to runners who did not meet the criteria for exercise dependence (50).…”
Section: The Endocannabinoid Systemmentioning
confidence: 99%
“…You et al [21] found that the gene expression of fatty acid amide hydrolase (FAAH), enzyme that degrades the N-acyl-ethanolamides, is lower in the abdominal adipose of obese women on a program combining exercise training and a caloric restriction diet. Dubreucq et al [22] reported CB1 knockout mice to display 30–40% less running behavior, and proposed a functional loop between the eCB system and MVPA.…”
Section: Introductionmentioning
confidence: 99%
“…In visceral adipose tissue there is greater mRNA expression of CB-1 than in subcutaneous adipose tissue (Bluher et al, 2006). Moreover, in obese individuals, 2-AG, CB-1 and MGL are up-regulated in abdominal adipose tissue, whereas their expression is downregulated in gluteal adipose tissue (Pagano et al, 2007;You et al, 2011). Collectively, current evidence indicates that the endocannabinoid system is dysregulated in obesity and greatly influences the storage of energy in different adipose tissue depots.…”
Section: Endocannabinoidsmentioning
confidence: 70%
“…The expression of the CB-1 receptor is also correlated with BMI and the metabolic syndrome (Sarzani et al, 2009). Overall the endocannabinoid system is dysregultaed in peripheral tissues in obesity, altering lipid and glucose metabolism (Pagano et al, 2007;You et al, 2011;Izzo et al, 2009). In visceral adipose tissue there is greater mRNA expression of CB-1 than in subcutaneous adipose tissue (Bluher et al, 2006).…”
Section: Endocannabinoidsmentioning
confidence: 95%